Der Hauptmann von Köpenick - Eichhorn, Bernhard 1904-1980 (Kinowelt Home Entertainment, 2006)
A lower class man's life changes dramatically when he finds an old captain's uniform and poses as a military official in Prussia.
Bildformat 1.33:1 (4:3 Vollbild)
Orig.: Bundesrepublik Deutschland, 1956
Enth. Filmdokumentation über Heinz Rühmann
Keywords: Zuckmayer, Carl -- 1896-1977 -- Der Hauptmann von Köpenick; Film; Comedy